2010
DOI: 10.1136/thx.2009.125849
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation of sleep apnoea by frequent central events in patients with the obstructive sleep apnoea syndrome at altitude: a randomised trial

Abstract: Background Many patients with the obstructive sleep apnoea syndrome (OSA) travel to the mountains for recreational and professional activities while temporarily discontinuing continuous positive airway pressure (CPAP) treatment. A study was undertaken to evaluate the hypothesis that altitude would aggravate their hypoxaemia, sleep-related breathing disturbances and impair daytime performance. Methods Thirty-four patients with OSA of median age 62 years (IQR 57e65), median apnoea/hypopnoea index (AHI) 47.5 even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 34 publications
2
44
0
1
Order By: Relevance
“…Our study demonstrated similar findings, but our participants who experienced altitude without PAP had less development of central apnea events than in previous studies, perhaps in part due to the administration of supplemental oxygen (4,7). Participants in the Burgess study ORIGINAL RESEARCH were exposed to simulated altitude over a 4-hour period before the 8-hour sleep study, to allow for greater hypoxic stimulus.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Our study demonstrated similar findings, but our participants who experienced altitude without PAP had less development of central apnea events than in previous studies, perhaps in part due to the administration of supplemental oxygen (4,7). Participants in the Burgess study ORIGINAL RESEARCH were exposed to simulated altitude over a 4-hour period before the 8-hour sleep study, to allow for greater hypoxic stimulus.…”
Section: Discussionsupporting
confidence: 66%
“…The partial pressure of oxygen of inspired air (PI O 2 ) decreases and hypoxemia increases with ascent (2,5,6). Altitude exposure in untreated patients with OSA worsens hypoxemia and increases sleep-related breathing disturbances due to frequent central apnea or hypopnea (7). One of the key physiological traits of sleep apnea is the presence of a hypersensitive ventilatory control system (high loop gain), characterized by a large ventilatory response to a change in ventilation.…”
mentioning
confidence: 99%
“…Since acclimatization duration has an important impact on Sp O 2 at a defined altitude [16,17,18], it was important that the recruited volunteers were residents of the college where they were studying, which was the case with each participant of this study. In both institutions, an air conditioning unit maintained the ambient temperature in the room at 23–25°C.…”
Section: Methodsmentioning
confidence: 99%
“…Another recent study 7 assessed the effects of increased altitude from baseline 490 m, with 2 nights each at 1860 m and 2590 m. Although there was a reduction in nocturnal oxygen saturation (94%, 90%, 86-87%, respectively), all patients ascended to altitude without CPAP, despite being CPAP dependant at baseline. In our report we assessed the longitudinal effects of acute changes in altitude from 820 m to 4400 m on CPAP levels and apneic/hypopneic episodes, while continuing to use CPAP.…”
Section: Discussionmentioning
confidence: 99%